The value of urgent care dermatology. (28th August 2018) - Sempler, Jessica; Thomas, Frank; Pettit, Jacob; Klein, Stephanie Z.
Abstract: Objective: To determine whether urgent care dermatology adds value (service + quality/cost) to healthcare. Methods: A retrospective cross‐sectional chart review of dermatologic patients in three service settings was compared: an urgent care dermatology clinic (same day dermatology [SDD]), the emergency department (ED), and a general dermatology clinic. Study period was July 1–September 30, 2014, for ED and SDD patients and August 2014 for general dermatology patients. ED patients had diagnoses of dermatitis (629.9) or rash (782). Final diagnoses, visit length, and no‐show rates were determined. Cost and charge data for patients seen in SDD versus the ED were provided by the university, without raw data available for publication. Results: For matched diagnoses, ED visits were 105 (95% CI: 68.7–152.4, P < 0.001) minutes longer than SDD visits. Compared to SDD, no‐shows in the general dermatology clinic were 2.24 times more likely (95% CI: 1.0003–5.02, P = 0.045). The odds for an SDD patient to be diagnosed with a code that was also seen in the ED was 13.0 (95% CI: 8.0–21.2, P < 0.01) times higher than the odds for the same diagnosis to be given to patients seen in the general dermatology clinic. ED visits cost 25% more than SDD visits. Patient charges for an ED visit are 207% more than for an SDD visit. Conclusions: Urgent care dermatology clinic adds value to the healthcare system by providing quality care and excellent service at low cost. Dermatologists better utilize their skills by seeing acute, often‐serious patients who would have otherwise been seen in the ED.